Compound Nouns in the German Terminology of the Border Guarding Sphere. - Dudok, Roman; Tatarovska, Olesya; Tsyntar, Natalia; Tsviak, Larysa; Bloshchynskyi, Ihor (Applied Linguistics Research Journal, 2021)
Constant changes in all the spheres of human life certainly affect the process of development of the vocabulary of the language, because the new objects and concepts must be nominated, respectively, new lexical units are formed. Compounding is a common way of word formation in the German language. This phenomenon mostly affects nouns. In German, compound nouns are defined as composites, characterized by specific semantic and structural features as well as certain features of formation and functioning. In the field of border guarding (BG) and protection, German compound nouns function for the purpose of nominating the relevant border concepts.
Keywords: Border, Schengen, terminology, German, compound noun, structure, gender